The impact of the diurnal cycle on the propagation of Madden‐Julian Oscillation convection across the Maritime Continent. (8th October 2016) - Hagos, Samson M.; Zhang, Chidong; Feng, Zhe; Burleyson, Casey D.; De Mott, Charlotte; Kerns, Brandon; Benedict, James J.; Martini, Matus N.
Abstract: Influences of the diurnal cycle on the propagation of the Madden‐Julian Oscillation (MJO) convection across the Maritime Continent (MC) are examined using cloud‐permitting regional model simulations and observations. A pair of ensembles of control (CONTROL) and no‐diurnal cycle (NODC) simulations of the November 2011 MJO episode are performed. In the CONTROL simulations, the MJO signal is weakened as it propagates across the MC, with much of the convection stalling over the large islands of Sumatra and Borneo. In the NODC simulations, where the incoming shortwave radiation at the top of the atmosphere is maintained at its daily mean value, the MJO convection signal propagating across the MC is enhanced. Examination of the surface energy fluxes in the simulations indicates that the surface downwelling shortwave radiation is larger in the presence of the diurnal cycle (CONTROL simulations) primarily because clouds preferentially form in the afternoon and are smaller during day time in comparison to nighttime. Furthermore, the diurnal covariability of surface wind speed and skin temperature results in a larger sensible heat flux and a cooler land surface in the CONTROL runs compared to NODC runs. An analysis of observations indicates that ahead of and behind the MJO active phase, the diurnal cycle of cloudiness enhances downwelling shortwave radiation and hence convection over the MC islands. This enhanced stationary convection competes with and disrupts the convective signal of MJO events that propagate over the waters surrounding the islands. Key Points: The diurnal cycle disrupts MJO propagation across the Maritime Continent It enhances downwelling radiation and precipitation over the MC islands It however has a net cooling effect on the MC land surfaces